3+6s-2=6s+3-2s

Simple and best practice solution for 3+6s-2=6s+3-2s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+6s-2=6s+3-2s equation:


Simplifying
3 + 6s + -2 = 6s + 3 + -2s

Reorder the terms:
3 + -2 + 6s = 6s + 3 + -2s

Combine like terms: 3 + -2 = 1
1 + 6s = 6s + 3 + -2s

Reorder the terms:
1 + 6s = 3 + 6s + -2s

Combine like terms: 6s + -2s = 4s
1 + 6s = 3 + 4s

Solving
1 + 6s = 3 + 4s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-4s' to each side of the equation.
1 + 6s + -4s = 3 + 4s + -4s

Combine like terms: 6s + -4s = 2s
1 + 2s = 3 + 4s + -4s

Combine like terms: 4s + -4s = 0
1 + 2s = 3 + 0
1 + 2s = 3

Add '-1' to each side of the equation.
1 + -1 + 2s = 3 + -1

Combine like terms: 1 + -1 = 0
0 + 2s = 3 + -1
2s = 3 + -1

Combine like terms: 3 + -1 = 2
2s = 2

Divide each side by '2'.
s = 1

Simplifying
s = 1

See similar equations:

| 6/(11y-1)=3/(5y-1) | | 5x/9=(x-5)/45 | | (w-y/2)(2) | | 9x+1=5x+11 | | (X-0.1)+1= | | 2y(4-2)=2/2 | | 6v+24=-4(7+5v) | | 7x-2+2x+8=180 | | -6x+4(3x+6)=26+4x | | 24-4n=-5(4-8n) | | 7+2y=5 | | 9+5+2k=6k-7 | | -(2v+2)=-12-7v | | x-2x^2=4x-4 | | 6x-21=3x-12 | | -16(4a-9b+2c)= | | (14/3)x=-126/11 | | 4(n+4)=-2+7n | | 4.2x+4=25 | | 5(x)X(25)2x=5 | | (957/14)x=18 | | 2(3x+5)+2(8x-7)=180 | | 112x5/14 | | (22/3)x=7 | | 5x-2=41 | | 9e^4x=196 | | 5g+3.29=25.24 | | .069x+x=20 | | 4.905x*x=11 | | 127+x+(x-10)+(x-3)=180 | | .06x-2=3+0.4x | | -48+11n-20n+12=0 |

Equations solver categories